Dorsal Approach to Septum in External Septorhinoplasty - Ozturan, ORHAN; ÖZTURAN, ORHAN; Dogan, REMZİ; DOĞAN, REMZI; AKSOY, Fadlullah; AKSOY, FADLULLAH; TUGRUL, Selahattin; Eren, SABRİ BAKİ; EREN, SABRİ BAKİ (My University, 2014)
Objective: During external septorhinoplasty, access from the caudal septum into subperichondrial space often poses difficulties and challenges for proper elevation of the mucoperichondrial flap. The dorsal and caudal approaches were compared with respect to duration and mucosal integrity.